Recent trends of indian student migration to the European Union: brain drain or brain gain? - Chawla, Varsha (2018)
The European Union (EU) has maintained relations in key strategic areas with India since the 1960s. Education has played an important role in the diplomatic relations between India and the EU. Non-European student mobility to the countries of the EU has significantly increased in recent years and India has been a major source of student mobility to the EU leading to education becoming a service increasingly tradable. This dissertation focuses on student migration between India and the EU, contributing to improving the understanding of the recent trends of India-EU migration, mainly characterized by a shift in the Indian students’ choices of the European destination for higher education; from a more traditional choice, the United Kingdom to a steadily rising preference for Germany and the factors influencing such choices. The study identifies the socio-economic factors determining the outflows from India and the inflows to the EU, attempting to ascertain whether Indian students return to India post completion of studies in the EU to look for further career prospects or prefer to settle in the host country in the EU and thus, if the current trends of student migration are leading to a short term brain gain in the EU but an overall reverse brain drain in India; Tendências Recentes da Migração de Estudantes Indianos para a União Europeia: Fuga de Cérebros ou o seu Contrário? Resumo: A União Europeia (UE) mantem desde a década de 60 do passado século ligações com a Índia em áreas chave, tendo a educação desempenhado um papel importante nas relações diplomáticas entre ambos. A mobilidade dos estudantes estrangeiros para os países da UE aumentou significativamente nos últimos anos, sendo a Índia um dos principais países de origem destes fluxos. Esta dissertação centra-se na migração de estudantes entre a Índia e a UE, contribuindo para melhorar a compreensão das tendências recentes na migração Índia-UE, caracterizada principalmente por uma mudança nas escolhas dos alunos indianos do destino europeu para o ensino superior, da escolha mais tradicional, Reino Unido, para uma crescente preferência pela Alemanha, e aos fatores que influenciam essas escolhas. O estudo identifica os fatores socio-económicos que determinam as saídas da Índia e as entradas para a UE, tentando verificar se os estudantes indianos retornam à Índia após a conclusão de estudos na EU, para procurar novas perspectivas de carreira, ou preferem estabelecer-se no país anfitrião e, portanto, se as tendências atuais da migração estudantil estão a traduzir-se em brain gain de curto prazo para a EU e a brain drain na Índia.